Influência do tratamento com abatacept na remodelação óssea pós exodontia e em parâmetros vasculares na polpa dentária de ratos - Mesquita, Karine Cestaro (2022)
Abatacept is a recombinant protein that has been approved for the treatment of rheumatoid arthritis. This drug selectively modulates the costimulatory signal necessary to activate T lymphocytes, reducing the expression of pro-inflammatory cytokines. However, secondary effects such as increased bone deposition, delayed healing of oral ulcers, and reduced angiogenesis and endothelial adhesion have been observed, with the latter finding being possibly related to its recycling and elimination by FcRn-type receptors. Therefore, the aim of the present study was to evaluate the influence of treatment with abatacept on bone remodeling after tooth extraction and vascular parameters of the dental pulp of Wistar rats. A total of 64 male Wistar rats were equally divided into a test group, which received subcutaneous (SC) administration of abatacept 8mg/kg/week, and a control group (SC), which received equivolumetric saline injections of 0.1ml/kg /week. The extraction of the lower left first molar was performed on the 15th day after abatacept/saline administration, with surgical difficulty being assessed during the procedure, followed by euthanasia on days 3, 7, 14, and 28 after surgery (n=8/group/day of euthanasia). The mandibles of the rats were removed, and the left hemimandible was submitted to radiographic, histological, and immunohistochemical evaluation (TRAP, CD3+, FoxP3+, OPG, RANK, and RANKL). Data were analyzed by oneway ANOVA and two-way ANOVA followed by Bonferroni post hoc test considering p<0.05 as significant (GraphPad Prism 5.0). The right hemimandibles of animals euthanized on day 28 were also assessed to evaluate the pulp of the mandibular first molar. The specimens were histologically processed (Hematoxylin-eosin), and photomicrographs at 400× magnification of the dental pulps were captured for histomorphometric analysis. Total pulp area, total and individual blood vessel area, cellularity, and immunohistochemistry for e-NOS, caspase 3 and FcRn markers were evaluated. Student's t or Mann-Whitney tests were used (p<0.05, GraphPad Prism 5.0). The evaluation of the left hemimandible showed no significant difference regarding surgical difficulty; however, radiographically, there was a delay in bone deposition in the abatacept group (p= 0.012), with histological changes reflected by a reduction in the number of polymorphonuclear (PMN) (p= 0.028) and mononuclear (MN) cells (p= 0.004) and delay in the involution of MN cells (p = 0.003). The number of osteoclasts (p= 0.009) and TRAP+ multinucleated cells (p= 0.001) reduced significantly, and, although treatment with abatacept did not interfere in the number of vessels, it was associated with increased immunoexpression of CD3+ (p= 0.038), FoxP3+ (p= 0.002), OPG (p= 0.003), and RANK (p = 0.022) as well as a reduction in the immunoexpression of RANKL (p= 0.013). Conversely, in the right hemimandible, the dental pulps of animals treated with abatacept showed an increase in the number of vessels (p= 0.004), with a smaller mean vessel area (p = 0.002) and an increase in pulp cellularity (p= 0.003), in addition to a reduction in the immunoexpression of e-NOS (p=0.007) in odontoblasts and an increase of caspase 3 positivity (p= 0.021). Therefore, treatment with abatacept delays post-extraction bone formation through Treg responses and osteoclastogenesis inhibition because of a dysregulation in the RANK/RANKL/OPG axis. Furthermore, in the dental pulp, the use of this drug induced a reduction in the diameter of blood vessels with a consequent increase in the number of vessels and cellularity, apparently associated with a reduction in e-NOS and an increase in caspase 3 expression. The immunoexpression of Fc-Rn in odontoblasts and pulp endothelial cells was also observed.